(untitled) (Journal of NELTA, 2010)
This paper aims to highlight the process of selecting a research topic through the identification of broad area and then narrowing it down to the research title. The article starts with the brief introduction to research and its micro activities. It also clarifies that topic selection is the base for all other microactivitie. The focus is laid on reviewing the literature as the preliminary step in the selection of research topic. In order to facilitate the new researchers and to remind the experienced ones, a list of some possible broad areas in applied linguistics is presented. Before concluding the article, I have argued that without reading and reviewing the existing literature topic selection is very difficult. Key words: Research problem, research process, micro activity, broad area, specific area DOI: 10.3126/nelta.v14i1.3087 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 21-25